Soil physical properties as indicators of histosol degradation in Colombia - Aguillon-Estacio, Ricardo Javier; Muñoz-España, Irene Alejandra; Guerra-Acosta , Adriana del Socorro; Bolívar-Gamboa, Adriana; Pinzón-Sandoval, Elberth Hernando (Revista de Ciencias Agrícolas, 2024)
Changes in soil utilization exert detrimental effects on its properties, emphasizing the critical need for a thorough evaluation to mitigate their repercussions on the ecosystem. This investigation was conducted aiming to assess the physical degradation in histosol soils in the Putumayo department, Colombia, caused by alterations in land use. For this, we assessed two types of areas: those without intervention (T0) and those affected by deformation in mound structures caused by the combined actions of livestock and high moisture, commonly known as “tatucos”. The assessment categorized these areas based on the percentage deformation incidence: low degradation (T1), moderate degradation (T2), and high degradation (T3). Sampling was conducted at a depth of 15 cm, both in the tatuco-affected zone and its surrounding area. Measurements were taken for mound height and diameter, as well as physical properties such as bulk and real density, porosity, volumetric moisture, penetration resistance, and the degree of organic material decomposition. The primary land use identified in the study area was extensive livestock farming. It was established that in areas with high levels of degradation (T3), there was an average mound diameter of 151.9 ± 4.46 cm and a height of 22.7 ± 2.59 cm. Regarding physical properties in the area adjacent to the mound, there was a bulk density of 0.24 g.cm-3, a real density of 1.62 g.cm-3, and a penetration resistance of 0.71 MPa. These values were significantly higher than those observed in areas without intervention. Hence, it can be inferred that the alteration in land use is causing a substantial change in the physical properties of these soils, which are vital for the agroecosystems in the southern regions of Colombia.